Seismic-resilient diagrid structures with hybrid buckling restrained braces. (May 2022) - Heshmati, Mahdi; Tameh, Mohammadreza; Khatami, Alireza
Abstract: Typical diagrid systems inherently possess significant structural strength and stiffness, yet buckling of diagonal members is highly probable under seismic loadings which sequentially leads to a brittle behavior. Thus, in this study, the seismic resilience of typical diagrid structures is improved by proposing an innovative type of buckling restrained braces called "Hybrid Buckling Restrained Brace" (HBRB). Unlike the standard buckling restrained braces, HBRB is erected by at least two different steel materials, low yield point (LYP) steel and high-performance steel (HPS) in a single core. To this end, a set of 32 diagrid models with different configurations are designed and simulated numerically. Nonlinear static analysis and incremental dynamic analysis are conducted based on the FEMA P695 methodology to assess the ductility factor, over-strength factor, collapse safety and self-centering capacity of diagrid archetypes. Results indicate that the application of HBRBs significantly improve the seismic response of the diagrid structures. This is due to the early yielding of low yield point (LYP) steel material lead to improving the ductility of hybrid diagrid structures; and application of high performance steel (HPS) material lead to enhancing the post-yield stiffness of diagrid structures. Moreover, employing the HBRB increases the response modification factor (R), collapse margin ratio (CMR) and re-centering characteristic of diagrid structures. The findings of this study can assist structural designers to decide an appropriate form of HBRB in the height of diagrid structures.